Thinning Intensity and Pruning Impacts on Eucalyptus Plantations in Brazil. (13th January 2015) - Nogueira, Gilciano Saraiva; Marshall, Peter L.; Leite, Helio Garcia; Campos, João Carlos Chagas
Abstract : A thinning intensity experiment using the Eucalyptus grandis × E. urophylla hybrid was conducted at three sites in Bahia State, Brazil. The treatments were a combination of thinning intensities and pruning: 20%, 35%, and 50% basal area removed with no pruning and 35% basal area removed plus pruning (at 27 months). Plots were measured roughly annually from 27 to 165 months. Thinning was implemented on all sites at 58 months and again at 142 months at two of the sites. One of the sites was harvested at 87 months of age. A linear mixed model was applied separately to each installation to test for differences among treatments for mean increment of height, dominant height, quadratic mean diameter, and volume outside bark at the plot level. Additionally, differences in mean monthly increment of basal area and volume outside bark as a percentage of the value at the beginning of the increment period were examined. Increased thinning intensity increased all tree-level variables except dominant height. Pruning had no impact. Observed mortality on all plots was quite low. Thinning intensity response varied among sites and with time since thinning; however, the thinning intensity response was consistent through time among the installations.